Penerapan Intradialytic Stretching Exercise dalam Mengurangi Kram Otot pada Pasien Chronic Kidney Disease yang Menjalani Hemodialisa di Kota Palembang - Aprillia Nauli; Aniska Indah Fari; Dheni Koerniawan (STIKES Columbia Asia Medan, 2026)
Chronic Kidney Disease (CKD) is a progressive condition characterized by a gradual decline in kidney function, often requiring hemodialysis therapy. One of the most common complications experienced during hemodialysis is muscle cramping, particularly in the lower extremities, which can reduce patient comfort and interfere with the effectiveness of treatment. Intradialytic Stretching Exercise is a non-pharmacological intervention that has been shown to help reduce muscle cramps in hemodialysis patients. To analyze the implementation of Intradialytic Stretching Exercise in reducing muscle cramps among patients with CKD undergoing hemodialysis. This case study used an Evidence-Based Practice (EBP) approach involving a CKD patient on hemodialysis who experienced muscle cramps. The intervention consisted of Intradialytic Stretching Exercise performed for 20 minutes, twice a week during hemodialysis sessions. Muscle cramp levels were assessed using the Cramp Questionnaire Chart before and after the intervention. The implementation of Intradialytic Stretching Exercise resulted in a reduction in muscle cramp severity. Previous studies supporting this EBP intervention demonstrated significant improvements in the frequency, duration, and intensity of muscle cramps following regular intradialytic stretching exercises. Intradialytic Stretching Exercise is an effective non-pharmacological intervention for reducing muscle cramps in patients with CKD undergoing hemodialysis. Hemodialysis nurses are encouraged to incorporate Intradialytic Stretching Exercise into routine nursing care and provide patient education to promote regular exercise participation, thereby preventing and reducing muscle cramps during hemodialysis.